MECHANISMS OF PLANT ADAPTATION TO PHOSPHORUS (American Journal of Technology and Applied Sciences, 2023)
Phosphorus is one of the seventeen essential nutrients required for plant growth. Despite its importance, it is limiting crop yield on more than 40% of the world's arable land. Moreover, global P reserves are being depleted at a higher rate and according to some estimates, there will be no soil P reserve by the year 2050. This is a potential threat to sustainable crop production. Most of the P applied in the form of fertilizers may be adsorbed by the soil and is not available for plants lacking specific adaptations.